The Effects of Exercise Intensity on Non-Exercise Physical Activity - Stein, John (East Carolina University, 2020)
Cardiometabolic diseases are some of the leading causes of death in the United States with African Americans being at greater risk of mortality from these diseases. Physical inactivity has been shown to be a risk factor for cardiometabolic diseases. Increased levels of non-exercise physical activity has been shown to influence cardiometabolic risk factors. PURPOSE: The purpose of the present study is to examine the effects of exercise intensity on non-exercise physical activity. As well as examine the effects of increased levels of non-exercise physical activity on cardiometabolic risk factors. METHODS: An all African American sample was recruited and randomized into three groups: control (n=15), moderate-intensity exercise (n=12), high-intensity exercise (n=12). The two exercise groups participated in 24 weeks of aerobic exercise with each group exercising at their assigned intensity. The moderate-intensity group exercised at a HR associated with 50% of their VO2max and the high-intensity group exercised at a HR associated with 75% of their VO2max. Non-exercise physical activity was assessed using a Fitbit Flex that was continuously wore by all participants except during exercise sessions. An analysis of variance (ANOVA) was used to determine if there were between group differences in steps, light-intensity physical activity, and MVPA. To analyze change in steps, light-intensity physical activity, and MVPA and other cardiometabolic risk factors, a pearson's correlation was utilized RESULTS: There were no significant changes in non-exercise physical activity variables and cardiometabolic risk factors between groups but the change in VO2peak was significantly higher in the high-intensity group compared to the control group (p[less-than-orequal-to]0.05). For the moderate-intensity group, change in fat mass and change in time in vigorous-intensity (r=-0.61 p>.05) and MVPA (r=-0.58 p[less-than].05). For the high-intensity group, change in triglycerides and time in vigorous-intensity (r=0.61 p[less-than].05) and change in glucose and steps (r=0.58 p[less-than].05) and time in light-intensity (r=0.65 p[less-than]0.05) for high intensity. After splitting the data into tertiles based on change in steps, there was significant between group differences change in steps(p[less-than-or-equal-to]0.001), time in light-intensity(p[less-than-or-equal-to]0.001), time in moderate-intensity(p[less-than-or-equal-to]0.01), time in vigorous-intensity(p[less-than-or-equal-to]0.01), time in MVPA(p[less-than-or-equal-to]0.01). As well the between group change in weight (p=0.08) and BMI (p=0.083) approach significant. CONCLUSION: In the present study, no compensatory effect of starting a moderate- or high-intensity aerobic exercise was seen on non-exercise physical activity. Additionally, there were benefits to cardiometabolic risk factors with increased levels of non-exercise physical activity, specifically fat mass. Further examination of the effects of non-exercise physical activity on African Americans and other populations is warranted.
Keywords: Exercise--Physiological aspects; Cardiovascular system--Diseases--Prevention; Bioenergetics; African Americans--Health and hygiene